HARMONISASI FIKIH KELUARGA DAN HUKUM POSITIF: STUDI PERBANDINGAN PEMBATASAN USIA PERKAWINAN DI INDONESIA DAN MALAYSIA - Puji Azizah, Faras; Alim Usman, A’zhami; Afifah Syabilah, Nur (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This article discusses the Analysis of a Comparative Study of the Law on the Restriction of the Marriage Age in Indonesia and Malaysia. This study aims to compare the laws restricting the age of marriage in the two countries. This study uses a literature study method by collecting sources from books, journal articles, and relevant themes. The results of this study show that there is a difference between the laws restricting the age of marriage in Indonesia and Malaysia. In Indonesia, the minimum age limit is 19 years old for boys and girls, while in Malaysia, the minimum age limit for girls is 16 years old and 18 years old for boys. In addition, the study also highlighted that the marriage age restriction in Indonesia reflects gender equality, while in Malaysia a lower age is set to anticipate the risk of pregnancy out of wedlock, elopement, and similar problems. Not only that, by setting a minimum age limit, the law seeks to protect the welfare of children and ensure that marriage occurs at a mature and responsible age so that children born can grow up in a healthy and stable environment.